Bean Program: The VEF(IBN)-EP-IBYAN scheme - International Center for Tropical Agriculture (2016)
To assure proper evaluation of all materials to be distributed internationally, the CIAT Bean Program designed a sequential process of germplasm evaluation and distribution known as the VEF-EP-IBYAN scheme. VEF (for the Spanish acronym of Bean Team Nursery) was an observational nursery; EP (Spanish acronym for Preliminary Trial) a regional yield trial and IBYAN the international yield trial. The scheme worked as follows: The advanced lines (hereinafter referred to as F4) were evaluated under the VEF - EP (both at the national level) - IBYAN (at the international level) scheme. Early generations, in contrast, were handled through a regional division of labor. Breeder I generated materials for Central America and the Mexican humid tropics; breeder II for the Andean Region, the Caribbean, and Africa; and breeder III, for Brazil, Northwest Argentina, the semiarid areas of Mexico, and Western Asia. Each breeder made the necessary contacts with breeders of the targeted regions to support them in developing bean populations according to specific requests and to provide them with sources of resistance to major production constraints. One golden rule followed was that no breeder would send early generation materials to countries outside his work areas to avoid overwhelming national programs with huge amounts of genetic material still being developed. To benefit national programs with the materials produced by all breeders, the Program established that they should deliver their best F4 to be evaluated for one year in the VEF by the entire bean team (pathologist, entomologist, virologist, plant physiologist, and agronomist). The best-performing VEF materials continued on to preliminary yield trials (EP), which, at the same time, served as a basis for selecting those lines that would enter the IBYAN. The three nurseries were at the disposal of the national programs that, accordingly, received the best advanced materials of the three CIAT bean breeders through this channel. The VEF later changed its name to IBN (International Bean Nursery). The VEF(IBN)-EP-IBYAN scheme ceased operating in 1996.